Efficiency of Private Secondary Education Services for Some Major Cities in Basra Governorate for the Academic Year (2019-2020) - Mahdi Katami Kazem, . Ghaida; Abdul-Amir Abboud Al-Zayer, Prof. Dr. Adel (Basra studies journal, 2023)
The efficiency of private secondary education services was studied for some of the main cities in Basra Governorate, represented by the city (Al-Madina, Al-Qurna, Al-Dair, Al-Haritha, Abi Al-Khasib, Al-Zubair, Al-Faw) for the academic year (2019-2020). The study included the geographical distribution of private secondary schools according to the main cities and the efficiency of its services in accordance with the local planning standards set by the Iraqi Ministry of Education, and the results of the standards showed that they conform to the local planning standard in terms of educational and spatial indicators, but in terms of social indicators, they do not conform to the planning standards.